Body Language in Polish and Russian Phraseology - Hordy, Mirosława (Poznańskie Studia Slawistyczne, 2020)
The article addresses the issue of a body language as a semiotic code and its reflection in systems of natural languages, in their phraseological resources. The material for analysis is phraseological units of contemporary Polish and Russian languages. The basis for comparison is the phraseological concept by Weronika N. Telia (В.Н. Телия) and linguistic works by Grigorij E. Krejdlin (Г.Е. Крейдлин). First and foremost, three types of signs of the body language are verbalised in subsystems under analysis: bodily symptoms, symptomatic and communicative gestures and a body position.